Lipid accumulation product better predicts metabolic status in lean polycystic ovary syndrome than that by visceral adiposity index - Hurjahan Banu; Md Shahed Morshed; Tania Sultana; Sukanti Shah; Shazia Afrine; M A Hasanat (Wolters Kluwer Medknow Publications, 2022)
Background: Both visceral adiposity index (VAI) and lipid accumulation product (LAP) can be used to assess insulin resistance (IR) and metabolic syndrome (MetS) which are required for management of even lean polycystic ovary syndrome (PCOS) (body mass index [BMI] <23 kg/m2). Aim: This study was aimed to see the magnitude of associations of VAI and LAP with cardiometabolic risk factors including IR and MetS in lean PCOS. Study Setting and Design: This cross-sectional study was done amongst 62 newly detected lean PCOS patients and 58 age- and BMI-matched healthy controls. Materials and Methods: PCOS was diagnosed according to the Revised 2003 Rotterdam Consensus criteria. Along with relevant clinical data, fasting blood was taken to measure glucose, insulin and lipid profile by glucose oxidase, chemiluminescent microparticle immunoassay and by glycerol phosphate dehydrogenase-peroxidase method, respectively. IR was calculated by homeostasis model of IR (HOMA-IR). VAI and LAP were calculated from BMI, waist circumference, triglyceride and high-density lipoprotein cholesterol by using sex-specific formulae. Statistical Analysis Used: Linear and binary regression analyses and receiver operating characteristics curve (ROC) analyses were done as appropriate. Results: Only LAP had predictive associations with age, systolic and diastolic blood pressure and total and low-density lipoprotein cholesterol. Both VAI and LAP had predictive associations with history of subfertility and MetS. LAP had moderate discriminating index for IR with cut-off of HOMA-IR of 2.3. Both VAI and LAP had excellent discriminating index for MetS in lean PCOS patients. Conclusions: LAP had more associations with cardiometabolic risks than VAI and was a moderate discriminator of IR in lean PCOS.